Design, synthesis and biological evaluation of pyrazolo[3, 4-b]pyridine derivatives as TRK inhibitors. Issue 1 (16th November 2022) - Liu, Nian; Wang, Xin; Fu, Qinglin; Qin, Qiaohua; Wu, Tianxiao; Lv, Ruicheng; Zhao, Dongmei; Cheng, Maosheng
Abstract : Based on scaffold hopping and computer-aid drug design, 38 pyrazolo[3, 4- b ]pyridine derivatives were synthesised. Among them, compound C03 showed acceptable activity with an IC50 value of 56 nM to TRKA kinase. Abstract : Tropomyosin receptor kinases (TRKs) are associated with the proliferation and differentiation of cells, and thus their continuous activation and overexpression cause cancer. Herein, based on scaffold hopping and computer-aid drug design, 38 pyrazolo[3, 4- b ]pyridine derivatives were synthesised. Further, we evaluated their activities to inhibit TRKA. Among them, compound C03 showed acceptable activity with an IC50 value of 56 nM and it inhibited the proliferation of the Km-12 cell line with an IC50 value of 0.304 μM together with obvious selectivity for the MCF-7 cell line and HUVEC cell line. Furthermore, compound C03 possessed good plasma stability and low inhibitory activity to a panel of cytochrome P450 isoforms except CYP2C9. Overall, C03 has potential for further exploration.